Association Between a Variable Number Tandem Repeat Polymorphism Within the DAT1 Gene and the Mesolimbic Pathway in Parkinson's Disease - du Plessis, Stefan; Bekker, Minke; Buckle, Chanelle; Vink, Matthijs; Seedat, Soraya; Bardien, Soraya; Carr, Jonathan; Abrahams, Shameemah (Frontiers in Neurology, 2020)
The loss of ventral striatal dopaminergic neurons in Parkinson’s disease (PD) predicts an impact on the reward system. The ventrostriatal system is involved in motivational processing and its dysfunction may be related to non-motor symptoms such as depression and apathy. We previously documented that patients with PD had blunted Blood Oxygen Level Dependent functional magnetic resonance imaging (BOLD fMRI) reward task related activity during both reward anticipation (i.e. in the ventral striatum) and reward outcome (i.e. in the orbitofrontal cortex). Evidence for the modulation of brain function by dopaminergic genes in PD is limited. Genes implicated in dopamine transmission, such as the dopamine transporter gene (DAT1) may influence the clinical heterogeneity seen in PD, including reward processing. This study therefore sought to determine whether genetic differences in the DAT gene are associated with brain activity associated with response to reward in PD patients and controls. A sample of PD cases on treatment (n=15) and non-PD controls (n=30) from an ethnic group unique to South Africa were genotyped. We found a three-way interaction between GENOTYPE X BOLD fMRI REWARD x DIAGNOSIS (F(1,40)=4.666, p=0.037, partial η2=.104). PD patients with the DAT1 homozygous 10/10 repeat genotype showed a relative decrease in orbitofrontal cortex reward outcome related activity compared to the patient group who did not have this repeat. PD patients with other genotypes showed an expected increase in orbitofrontal cortex reward outcome related activity compared to controls. Given the small sample size of the PD group with the 10/10 repeat, these results should be considered preliminary. Nevertheless, these preliminary findings highlight the potential modulation of dopamine transporter polymorphisms on the orbitofrontal reward system activity in PD and highlight the need for further studies.